Supporting a Sense of Connectedness: Meaningful Things in the Lives of New University Students - Bales, Elizabeth; Lindley, Siân (Proceedings of the 2013 ACM conference on Computer Supported Cooperative Work (CSCW 2013), 2013)
We report findings from interviews with new undergraduate students, in which they identified particular items as supporting a sense of connectedness with home. We characterize ways in which artifacts underpinned a sense of connection, including by conveying the character of the parental home, supporting a sense of continuity with it, and enabling a physical presence to be maintained there. We then consider how simple affordances offered by these artifacts, such as being able to move, position and sort them, enabled participants to reinforce the meanings that were associated with them. Such actions are normally taken for granted, but we describe how they are compromised for social media especially, due to functional limitations and questions of ownership. We highlight design opportunities for integrating the digital into physical space, and supporting the archiving and display of social media.